Apoptosis : mechanisms and role disease - Kumar, S (Springer, 1998)
This volume deals with many of the recent advances made in uncovering the molecular and cellular basis of apoptosis and elaborates on how this accumulating knowledge is helping us to understand the significance of apoptosis in pathogenesis of diseases arising from inappropriate cell death. Further, mechanistic aspects of cell death and role of apoptosis in disease is covered.
Results and problems in cell differentiation
Keywords: biologie; Cells; buňky; Disease; cytologie, klinická cytologie; nemoc